Export Entrepreneurship and Trade Structure in Latin America during Good and Bad Times - Fernandes, Ana M.; Lederman, Daniel; Gutierrez-Rocha, Mario (World Bank, Washington, DC, 2013)
The authors use a new dataset on export transactions for a large set of Latin American and Caribbean and comparator countries to assess the extent of "export entrepreneurship" during periods of fast export growth (2005-2007) and depressed external demand (2008-2009). Export entrepreneurship is equated with the extensive margin of exports, namely the advent of new exporting firms, new export products, and new export market destinations. The main findings are: (1) annual exporter entry, exit, and survival rates in Latin America and the Caribbean are quite similar to what is observed in other countries, and entry rates across sectors are quite similar but survival rates appear to be highest in agriculture; (2) the relative size of entrants into export markets (relative to incumbents) tended to be lower for natural resource-abundant countries during 2005-2007, but less so during the crisis years of 2008-2009; (3) entry rates tend to be lower in sectors in which a country has revealed comparative advantage, however, exit rates and survival rates of new exporters are higher in those sectors; and (4) the low growth of exports during the global recession of 2008-2009 in Latin America and the Caribbean was due to lower growth in exports of incumbent firms' pre-existing products and destinations, while new products and destinations tended to attenuate the recession's effects. Overall, the data suggest that the Latin American and Caribbean region appears to be no less entrepreneurial in terms of the extensive margins of exports than comparator countries.